Implementasi model project based learning dalam pembelajaran Bahasa Jerman di SMAN 8 Malang - Issabella, Baiq Tsania Avi Salwa; Maulero, Rount (Fakultas Sastra Universitas Negeri Malang, 2022)
In order to create an active and competitive young generation, Indonesia has established German as a foreign language taught at the SMA/MA level. Learning German is a form of awareness about the importance of mastering foreign languages in the 4.0 revolution era. Therefore, it is necessary to implement a variety of project based learning models in learning German in order to increase students' enthusiasm and activeness, develop student creativity, and assist students in communicating in cooperative work groups. This study aims to describe the course of the learning process with a project-based learning model and to determine student responses to the learning model. This type of research is qualitative with a descriptive approach. The subjects of this study were students of SMA Negeri 8 Malang who received German subjects. The data collection technique in this study used a digital questionnaire. The results of this study indicate that learning German using a project based learning model is effective and the majority of students state that teaching and learning activities are more interesting, exciting, and fun.